Kinerja Pegawai Bagian Layanan Pengembangan Usaha Dalam Penarikan Jasa Iklan Layanan Masyarakat Pada Kantor LPP RRI Bengkulu - Harianto, Defi; Imanda, Antonio; Yusuarsono, Yusuarsono (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the Performance of Employees of the Business Development Services Section in Attracting Public Service Advertising Services at LPP RRI Office of Bengkulu. The method used in this research is descriptive qualitative research. Furthermore, data collection techniques are carried out by means of interviews, observation and documentation. After obtaining the research results, it is analyzed by reducing data, presenting data and drawing conclusions. The informants in this study amounted to 5 people consisting of 2 key informants and 3 main informants. This research uses the theory according to Mahsun. (2006: 77) regarding performance theory: (1) Input indicators: There are costs used in making advertisements that are in accordance with PNPB rules, the amount of advertising costs depends on the collective agreement and how long the advertisement will be aired. (2) Process indicators: The public comes directly to the service section without a representative provided that a photocopy of a valid ID card or driver's license, fill out the form or stamp that has been provided, and pay the cost of making an advertisement based on existing regulations. (3) Output indicators: In terms of the target of making service advertisements determined by PNBP, it means that there are certain rules set by the President Director of LPP RRI. LPP RRI office of Bengkulu does not set targets in advertising, this is because LPP RRI Bengkulu emphasizes services according to community needs without pursuing profits. (4) Outcomes indicators: The production of advertisements for RRI services does not contain racial or ethnic groups, only for social purposes, including in serving the creation of advertisements desired by the community which have been regulated by the government through existing regulations including the amount of costs in making these service advertisements. (5) Benefit indicators: The benefits for the community in placing advertisements at LPP RRI Bengkulu are that the costs incurred are more affordable, the radio broadcast coverage is wider than other private parties and the advertisements broadcast are of higher quality. (6) Impact indicators: The effect for the community is that more people recognize the advertised product or service, while for the agency it can get income from the cost of advertising services made.